Inertial Sensing for Human Motion Analysis: Enabling Sensor-to-Body Calibration Through an Anatomical and Functional Combined Approach - Scattolini, Mara; Tigrini, Andrea; Verdini, Federica; Burattini, Laura; Fioretti, Sandro; Mengarelli, Alessandro (IEEE transactions on neural systems and rehabilitation engineering, 2025)
The use of inertial measurement units is gaining attention to estimate human joint kinematics. However, to obtain clinically meaningful results, sensor frame needs to be aligned with the underlying anatomical one. Although during the years different approaches have been proposed, a common consensus has not been reached. Further, inertial sensor positioning on human segments can affect frame definition and kinematics estimation. Thus, the aim of the present work is to define an anatomical calibration procedure for lower limb joints kinematics, robust with respect to sensor misalignment, and based on a limited set of movements, with static and functional assumptions. To this purpose, straight walking and turning motor tasks in six healthy subjects were considered, and results were compared with those provided by an optoelectronic system. Three sensor placements have been also evaluated to test the procedure with respect to sensor positioning. After offset removal, an average RMSE ≤2.5 deg in gait, and ≤2 deg in turning for all the configurations were obtained, outperforming results from previous approaches. Average offset values resulted about 6 deg for hip and ankle, whereas negligible for the knee. Outcomes of this study enable a simple and accurate measurement of clinically meaningful joints kinematics, also without a strict sensor placement.